The influence of canola oil biodiesel on performance, combustion characteristics and exhaust emissions of a small diesel engine - Mehmet Şen (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
In this work, the influence of canola oilbiodiesel addition to eurodiesel was evaluated on combustion, performance characteristicsand exhaust emissions of a single cylinder diesel engine. In the experiments,fuel mixtures obtained by adding 10%, 20% and 50% canola oil biodiesel (named COB10,COB20 and COB50 respectively) to eurodiesel fuel (COB0) were used.The test enginewas loaded at full load with electrical dynamometer and data was recordedbetween 1500 rpm and 3000 rpm at 500 rpm intervals. The result show thataddition of biodiesel to eurodiesel reducedcylinder pressure, engine torque and BTE while increased BSFC. Ignition delaydecreased slightly with the addition of biodiesel. NOx emission and smoke density wasdecreased as the biodiesel content increase in the fuel blends.